Loneliness in Gender-Diverse and Sexual Orientation–Diverse Adolescents: Measurement Invariance Analyses and Between-Group Comparisons. (April 2023) - McDanal, Riley; Schleider, Jessica L.; Fox, Kathryn R.; Eaton, Nicholas R.
Youth loneliness is a risk factor for myriad adverse psychosocial outcomes, making it a potentially informative construct for assessment and treatment research. Minority stressors may place LGBTQ+ (lesbian, gay, bisexual, transgender, and queer) youths at high risk of loneliness. However, the prevalence of loneliness across gender and sexual identities cannot be precisely estimated or compared without establishing that common measures assess the construct equivalently across groups. In a preregistered study, we determined the optimal structure of the UCLA Loneliness Scale and investigated whether it showed invariance across gender and sexual identities in a national U.S. sample of adolescents with elevated depressive symptoms ( N = 2, 431;https://osf.io/52ctd ). Results supported strict invariance, indicating that loneliness scores can be meaningfully compared across groups in this sample. Exploratory analyses indicated that loneliness levels and LGBTQ+ identity predicted levels of depression and anxiety. We discuss implications for research on loneliness, health disparities, and psychopathology in high-symptom youths.